Pengembangan Penilaian Pembelajaran PAI Berbasis Kecerdasan Buatan: Peluang dan Tantangan di MTs Durul Jazil - Anas Sofyan; Salito, Salito (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2024)
Islamic Religious Education (PAI) plays a vital role in shaping students' character and morals in Indonesia. In the digital era, artificial intelligence (AI) emerges as a potential tool to enhance the effectiveness of PAI learning assessments. This study aims to develop AI-based assessments for PAI at MTs Darul Jazil and explore the opportunities and challenges in its implementation. Using a qualitative descriptive approach, the research highlights AI's ability to provide objective, rapid data analysis, improving evaluation efficiency, reducing grading time, and delivering personalized feedback. These advantages support a more responsive and adaptive curriculum tailored to individual student needs and evolving educational demands. However, significant challenges include ethical concerns, data privacy issues, technological readiness, and educators' proficiency in AI usage. Addressing these requires targeted teacher training, robust ethical and privacy policies, and investment in reliable technological infrastructure. A comprehensive strategy enables MTs Darul Jazil to leverage AI, enhance education quality, and foster an effective and efficient learning environment.